TINJAUAN YURIDIS AKIBAT PERKAWINAN CAMPURAN TERHADAP ANAK - Widanarti, Herni (Fakultas Hukum, Universitas Diponegoro, 2019)
ABSTRACT In this Era of Globalization, people’s lives have increased greatly, the increasing number of nations has led to a country becoming open or having international relations with other countries. Mixed marriages have traversed all corners of the country and society, information globalization, economy, transportation, cyberspace have increased mobility by migrating from one country to another, causing people to meet and communicate with various different ethnic groups, cultures, religions and the customs and communication habits allow Indonesian citizens (WNI) to carry out marriage with foreign citizens (WNA) so that what is called mixed marriages arises. Mixed marriages result in legal consequences, including the legal relationship between parents and children, especially the legal status of child citizenship. Keyword : Mixed Marriage, Legal Status of Children, International Civil Law